Synthesis, photophysical properties and anticancer activity of micro-environment sensitive amphiphilic bile acid dendrimers. Issue 31 (9th March 2016) - Anandkumar, Devaraj; Raja, Rathinam; Rajakumar, Perumal
Abstract : Porphyrin-cored bile acid dendrimers containing deoxymethyl cholate and methyl cholate units at the periphery, have been synthesized by convergent methodology using a click chemistry approach and characterized by 1 H and 13 C NMR and MALDI-TOF MS data. Abstract : Porphyrin-cored bile acid dendrimers containing deoxymethyl cholate and methyl cholate units at the periphery, have been synthesized by convergent methodology using a click chemistry approach and characterized by 1 H and 13 C NMR and MALDI-TOF MS data. The absorption–emission behavior of dendrimers and its modulation under the influence of the dendritic environment is also investigated. The therapeutic efficacy of the bile acid dendrimers for the inhibition of the growth of tumor cells (MIA PaCa-2) increases as the dendrimer generation increases.